Extractive fermentation using aqueous two-phase systems for integrated production and purification of extracellular lipase derived from Burkholderia pseudomallei - Ooi, Chien Wei; Siew, Ling Hii; Mustapa Kamal, Siti Mazlina; Ariff, Arbakariya; Tau, Chuan Ling (Elsevier, 2011)
An extractive fermentation using aqueous two-phase partitioning system was developed in this study for the simultaneous cell cultivation and downstream processing of extracellular lipase derived from Burkholderia pseudomallei (B. pseudomallei). The B. pseudomallei growth and the enzyme production in different types of two-phase partitioning systems were investigated. An aqueous two-phase system (ATPS), which is composed of 9.6% (w/w) polyethylene glycol (PEG) 8000 and 1.0% (w/w) Dextran T500, provided the best conditions for the extractive lipase production. In this integrated process, biomass was accumulated in the bottom phase whereas the lipase was extracted to the top phase. High yield of 92.1% was recorded in the single batch operation. Repetitive batch of fermentation was progressively carried out by continuous replacement of the top phase every 24 h, which resulted in an average enzyme concentration of 16.5 U/ml for seven extractive batch over the duration of 168 h. The extractive fermentation in aqueous two-phase partitioning system is an attractive approach for the combination of the lipase production and the purification process, owing to the repeated use of the two-phase fermentation system and the ease of lipase recovery.